KESESUAIAN LAHAN INDUSTRI DENGAN SPATIAL MULTI-CRITERIA EVALUATION (SMCE) DAN FUZZY LOGIC DI KABUPATEN TABANAN, BALI - Yoga Dwi Putra, I Kadek; Wibowo, Adi (J SIG (Jurnal Sains Informasi Geografi), 2025)
Bali’s heavy reliance on tourism makes its economy vulnerable to external shocks, such as pandemics or natural disasters. Economic diversification through sustainable industrial development is a strategic effort to enhance Bali’s economic resilience. This study aims to assess industrial land suitability in Tabanan Regency using the Spatial Multi-Criteria Evaluation (SMCE) method and fuzzy logic within a Geographic Information System (GIS) framework. Five key criteria were evaluated: proximity to roads, rivers, settlements, slope gradient, and conservation areas. Results indicate that most of the region is classified as marginally suitable (51.84%) or unsuitable (21.36%), while 26.42% is suitable and only 0.38% is highly suitable for industrial development. One recommended area is Cau Belayu Village in Marga District, which meets technical standards and offers good accessibility. However, further assessments of ecological and social impacts are necessary. This study provides a scientific foundation for sustainable spatial planning in Tabanan, aligned with the Tri Hita Karana philosophy.